2012
DOI: 10.1016/j.jpcs.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal impurity effect on charge and spin density in iron: Ab initio calculations and comparison with Mössbauer data

Abstract: Short title: Transition metal impurity effect on charge and spin density in iron AbstractDensity functional theory was applied to study influence of the isolated impurity located on the regular site of the α-Fe crystal on the charge and spin density (hyperfine interactions) on the iron nucleus. Calculations were performed by using both pseudopotential and the full potential methods. The scalar relativistic approximation was applied. Perturbations of the charge and spin density on iron were calculated for all d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…They are similar to corresponding data given in the literature [22] and simultaneously they are at variance with the theoretical calculations based on density functional theory (DFT) [24]. (4) 0.690(13) 0.0058(5) 0.0010(2) 0.023 33.000(3) 0.688 (11) 0.0101(6) 0.0055(6) 0.034 32.850 (5) 0.620(16) 0.0081(6) 0.0017(4) 0.048 32.810 (7) 0.625(14) 0.0093(9) 0.0012 (5) …”
Section: Discussionsupporting
confidence: 89%
“…They are similar to corresponding data given in the literature [22] and simultaneously they are at variance with the theoretical calculations based on density functional theory (DFT) [24]. (4) 0.690(13) 0.0058(5) 0.0010(2) 0.023 33.000(3) 0.688 (11) 0.0101(6) 0.0055(6) 0.034 32.850 (5) 0.620(16) 0.0081(6) 0.0017(4) 0.048 32.810 (7) 0.625(14) 0.0093(9) 0.0012 (5) …”
Section: Discussionsupporting
confidence: 89%
“…[16] one can fi nd that for the Fe 0.985 Os 0.015 alloy B 1 = −3.60(3) T, B 2 < 0.5 T and IS 1 = −0.017(2) mm/s. In much recent work [18], it was found that the nearest neighbor single Os impurity reduces hyperfi ne magnetic fi eld on the iron nucleus by 3.97 T, while the second neighbor single Os impurity decreases this fi eld by 1.11 T. At the same time theoretical calculations based on density functional theory (DFT) give results which are different from the experimental ones; according to the calculations B 1 = −2.70 T, B 2 = −0.57 T, B 3 = 0.38 T, IS 1 = −0.010 mm/s, IS 2 = 0.033 mm/s and IS 3 = 0.004 mm/s [19].…”
Section: Experimental and Resultsmentioning
confidence: 84%
“…The Mössbauer spectrum of the sample after substitution 6% at Fe by Cr atoms only slightly changes at both room and nitrogen temperatures [12]. After the annealing at 700 K, the isomer shift decreases up to -0.101(2) mm/s and remains constant after annealing at 750 K. It could be caused by the decrease of distances between Fe and Cr atoms or/and the increase of Cr concentration.…”
Section: Resultsmentioning
confidence: 91%